Pengaruh Penyesuaian Kenaikan Njop Setiap Tahun Dan Kualitas Pelayanan Petugas Pajak Terhadap Kepatuhan Wajib Pajak Untuk PBB-P2 Di UPPRD Wilayah Kecamatan Kemayoran - Anggraeni, Via; Ramdan, Alief (Jurnal Ilmu Administrasi Publik, 2024)
This research was conducted because of the difference between PBB-P2 revenue and the realization target, as well as facts on the ground regarding the quality of service of officers with Taxpayer Compliance and was also supported by previous research, so this research is a confirmatory study. This study was conducted to find out how much influence the adjustment of the increase in NJOP every year and the quality of service of officers with Taxpayer Compliance for PBB-P2 in UPPRD Kemayoran District This study uses correlation and determination methods to see how much influence free variables and bound variables have. The population and samples in this study were taxpayers who were used as saturated samples, respondents were given statements using the Linkert scale. Based on the analysis of data carried out, it shows that between Variable X1 (Adjustment of NJOP Increase Every Year), Variable X2 (Quality of Officer Service and Variable Y (Taxpayer Compliance) has an influence so that the results of hypothesis testing that have been carried out in this study, concluded that the research hypothesis is "There is a positive and significant influence between" Adjustment of NJOP Increase Every Year and Quality of Service of Officers With Taxpayer Compliance For PBB-P2 in Kemayoran Subdistrict Area" although the influence is low, due to other factors that affect taxpayer compliance.